PENILAIAN POTOFOLIO DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR NEGERI KECAMATAN SUNGAI PINYUH - Dahlia, Dahlia; Marzuki, Marzuki; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to describe the planning, implementation, reporting and constraints in the assessment of portfolio. It was done in the qualitative descriptive method to obtain the detailed description of the portfolio assessment. The data collection techniques used were documentary study, observation and interview. The research subjects were the principals, teachers and learners. The research data revealed that portfolio assessment has been implemented in both public primary schools of Sei Pinyuh sub district. The research findings indicated that planning stage had been prepared by the teacher from the beginning of thematic learning phase. The implementation of the assessment made teachers improve their professionalism in compiling and recording learners’ learning achievement. Portfolio assessment reporting enabled learners to be more active and creative in the assigned work. The obstacles encountered were teacgers’ difficulties in managing the portfolio assessment process in sequence, due to the lack of understanding of portfolio assessment practicality. In conclusion, the application of portfolio assessment to thematic learning provided a change in the way teachers record students’ learning achievement, and enable them to improve their creativities in assigning tasks.Keywords: Assessment, Portfolio, Thematic Learning